Análise da adequação do ensino e da aprendizagem de inglês para fins específicos (IFE) no contexto dos cursos de tecnologia do IFCE - Carvalho, Adriana da Rocha (2022)
The aim of this study was to analyze if the English for Specific Purposes (ESP) course offered at undergraduate Information and Communications Technology (ICT) programs at the Federal Institute of Ceará (IFCE) is in compliance with the students’ needs. It is important to mention that the ESP course in Brazil is widely known as Inglês Instrumental. This approach, based on Language for Specific Purposes (LSP), has largely been adopted by many Brazilian universities as well as by the Federal Institutes once it claims to provide faster, more accurate and practical learning. Therefore, it seems more than relevant to evaluate if the current focused almost exclusively on developing the ability of reading meets the major stakeholders’ (students, academia, and the workplace) needs. In order to achieve this goal, we conducted a descriptive study using a quali-qualitative research methodology. The perspective of different stakeholders in the teaching-learning process provided a holistic perspective to the study. As Long (2005) points out, the triangulation of sources and methods is a powerful tool to identify the linguistic and communicative needs that help to design an effective LSP course. The corpus was, therefore, composed of 07 (seven) ESP teachers, 74 (seventy-four) undergraduate students, and 22 (twenty-two) subject-area teachers from 07 (seven) undergraduate ICT programs, besides 75 (seventy-five) ICT professionals. Firstly, an evaluation instrument was developed to analyze IFCE’ official guidelines for ESP teaching (PUD). The instrument was based on the different types of syllabuses described by Richards (2001), Basturkmen (2006), and Brown (2016), and on the methodology for ESP proposed by Dudley-Evans and St. John (1998) and Long (2005). Next, 04 (four) different questionnaires, one for each group of participant, were designed using Google Forms. The questionnaires were based on Hutchinson and Waters (1987), Dudley- Evans and St. John (1998), Long (2005), Basturkmen (2006), Huhta et al (2010), Flowerdew (2013), and Brown (2016). The questions aimed at investigating the perception of students, the ESP teachers, and the ICT teachers and professionals about the importance of the English language to academic and labor activities. The questionnaires also tried to identify the students’ English background knowledge, teachers’ knowledge of ESP approach, as well as the participants’ most important linguistic and communicative language needs for academic and professional activities. The analysis of the official guidelines for English courses at IFCE demonstrated that there is explicit orientation towards placing the focus of teaching on reading, besides being too synthetic in terms of relating ESP teaching to academic and professional activities. Also, data obtained from questionnaires suggested that, even though vocabulary knowledge and reading ability are highly relevant for the development of linguistic and communicative activities in academic and professional contexts, other abilities such as writing, listening, and speaking are equally important to perform in such situations. We can assume that there is a relative adequacy between what is taught in the ESP courses at IFCE and the undergraduate students’ English linguistic and communicative needs.